2017
DOI: 10.1136/jnnp-2017-315660
|View full text |Cite
|
Sign up to set email alerts
|

Rates and correlates of suicidal ideation among stroke survivors: a meta-analysis

Abstract: Despite some limitations, this meta-analysis shows that about one out of eight stroke survivors has suicidal ideation. Thus, there is enough evidence to support the use of routine screening and early interventions to prevent and treat suicidal ideation after stroke, especially among subjects carrying specific correlates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 39 publications
6
45
0
Order By: Relevance
“…However, Dollfus et al [30] suggested employing a sham coil, which may be a more reliable method for a placebo procedure. Last, the research group of Bartoli et al [31-34] showed that patients after stroke might be at an increased risk of suffering from depression, insomnia, and suicidal ideation. It would therefore be interesting to know, if and to what extent rTMS as adjuvant treatment to SLT might influence the emergence of psychiatric issues as outlined by Bartoli et al…”
Section: Discussionmentioning
confidence: 99%
“…However, Dollfus et al [30] suggested employing a sham coil, which may be a more reliable method for a placebo procedure. Last, the research group of Bartoli et al [31-34] showed that patients after stroke might be at an increased risk of suffering from depression, insomnia, and suicidal ideation. It would therefore be interesting to know, if and to what extent rTMS as adjuvant treatment to SLT might influence the emergence of psychiatric issues as outlined by Bartoli et al…”
Section: Discussionmentioning
confidence: 99%
“…Medical illness, including neurological disorders, may be an important risk factor for suicide . This risk may be related to the high prevalence of co‐occurring mood disorders that characterize medical illness, though the exact nature of the relationship between suicide risk and medical conditions is still unclear …”
Section: Introductionmentioning
confidence: 99%
“…A has suffered an injury resulting from a recent stroke, and her experience is not uncommon. Stroke is a leading cause of long‐term disability worldwide, and the literature suggests an association with depression, suicidal ideation, and suicidality [2,3]. Depression occurs after stroke more than any other physical illness and is the most recurrent psychiatric complication among poststroke patients—possibly as an organic process resulting from a brain injury—and there is an association with suicidality within the first 2‐5 years [3].…”
Section: Stroke Suicide and Professional Dutymentioning
confidence: 99%
“…Depression occurs after stroke more than any other physical illness and is the most recurrent psychiatric complication among poststroke patients—possibly as an organic process resulting from a brain injury—and there is an association with suicidality within the first 2‐5 years [3]. The frequency of depression and suicidal ideation is significant (about 12%) and should be a part of the screening, referring, and monitoring of patients with stroke [2].…”
Section: Stroke Suicide and Professional Dutymentioning
confidence: 99%